2010
DOI: 10.1161/strokeaha.109.576140
|View full text |Cite
|
Sign up to set email alerts
|

Off-Label Thrombolysis Is Not Associated With Poor Outcome in Patients With Stroke

Abstract: Background and Purpose-Numerous contraindications included in the license of alteplase, most of which are not based on scientific evidence, restrict the portion of patients with acute ischemic stroke eligible for treatment with alteplase. We studied whether off-label thrombolysis was associated with poorer outcome or increased rates of symptomatic intracerebral hemorrhage compared with on-label use. Methods-All consecutive patients with stroke treated with intravenous thrombolysis from 1995 to 2008 at the Hels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
186
2
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(209 citation statements)
references
References 27 publications
14
186
2
7
Order By: Relevance
“…34,35 Although the sHT rate in the elderly who were given thrombolysis was higher than in the younger in our study, as previously reported, 11,12,17,19 neither the adjusted ORs were apparently different (5.27 in the aged ≥80 and 4.52 in the aged <80), nor there was signifi cant interaction between age group and thrombolysis (P=0.86). The VISTA group did not report the analysis results about sHT.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…34,35 Although the sHT rate in the elderly who were given thrombolysis was higher than in the younger in our study, as previously reported, 11,12,17,19 neither the adjusted ORs were apparently different (5.27 in the aged ≥80 and 4.52 in the aged <80), nor there was signifi cant interaction between age group and thrombolysis (P=0.86). The VISTA group did not report the analysis results about sHT.…”
Section: Discussionsupporting
confidence: 60%
“…[19][20][21] For making evidence, a randomized controlled trial for thrombolysis to the elderly stroke patients is the best choice, but it has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] There are also now randomized trial data from the Third International Stroke Trial (IST-3), which enrolled patients for whom there was equipoise regarding the benefits of thrombolytic therapy and randomized to treatment with IV tPA versus placebo ≤6 hours from onset. 16 This study included 1617 patients aged >80 years and found that although the rate of good outcome in that group was overall lower than younger patients, there was still a significant benefit to treatment with IV tPA.…”
Section: September 2014mentioning
confidence: 99%
“…The license of intravenous recombinant tissue plasminogen activator (rt-PA) in the European Union is restricted to patients aged 80 years or less in many countries, but most centres do not follow this rule anymore 37 . According to the results from the 3 rd International Stroke Trial 38 and the updated meta-analysis 39 that proved the efficacy of rt-PA in patients aged 80 years or more, the use of rt-PA for elderly patients in clinical practice has increased.…”
Section: Intravenous Recombinant Tissue Plasminogen Activator (Rt-pa)mentioning
confidence: 99%